Is it time to turn our attention toward central mechanisms for post-exertional recovery strategies and performance? - Rattray, Ben; Argus, Christos; Martin, Kristy; Northey, Joseph; Driller, Matthew (Frontiers in Physiology, 2015)
Post-exercise recovery has largely focused on peripheral mechanisms of fatigue, but there is growing acceptance that fatigue is also contributed to through central mechanisms which demands that attention should be paid to optimising recovery of the brain. In this narrative review we assemble evidence for the role that many currently utilised recovery strategies may have on the brain, as well as potential mechanisms for their action. The review provides discussion of how common nutritional strategies as well as physical modalities and methods to reduce mental fatigue are likely to interact with the brain, and offer an opportunity for subsequent improved performance. We aim to highlight the fact that many recovery strategies have been designed with the periphery in mind, and that refinement of current methods are likely to provide improvements in minimising central fatigue. Whilst we offer a number of recommendations, it is evident that there are many opportunities for improving the research, and practical guidelines in this area.